Learning to Exercise by Imitation in Children Aged 6-7 - B.C. Rata; M. Rata; G. Rata (Editura Universitatii Transilvania din Brasov, 2022)
The present study is experimental research, conducted on children aged 6-7 years, included in preparatory classes, based on the learning and implementation of the theoretical and practical information with the help of "live demonstration" and "iconographic demonstration", therefore relying on imitation. In Physical Education, the quickest and easiest way for children to learn is through imitation. The analysis of the results showed that in the experimental group the use of the "live demonstration" leads to a greater increase in the number of pupils who can memorise and perform more related items than in the control group, which used the iconographic demonstration.